Grafting of Group‐10 Organometallic Complexes on Silicas: Differences and Similarities, Surprises and Rationale. Issue 10 (16th September 2022) - Gioffrè, Domenico; Rochlitz, Lukas; Payard, Pierre‐Adrien; Yakimov, Alexander; Copéret, Christophe
Abstract: Surface organometallic chemistry (SOMC) represents a unique synthetic platform for the preparation of model heterogeneous catalysts resembling those broadly applied in industry. SOMC techniques usually rely on the grafting of tailored molecular precursors onto the surface OH groups of oxide supports. The development of such precursors and the understanding of their reactivity with the supports are therefore crucial for the development of well‐defined surface species. While a large number of organometallic precursors of early transition metals are known, only few examples of group‐10 metal complexes are reported, in spite of the great interest for heterogeneous catalysts based on the Pt‐group elements. Herein, we report the reactivity of a family of group‐10 (Ni, Pd and Pt) alkyl complexes, towards partially dehydroxylated SiO2 yielding well‐defined supported species. We studied the effect of the metal, ligand, and support on the grafting mechanism of such precursors through a combined experimental and computational approach. Ultimately, we showed that at least two grafting pathways are possible for these compounds, namely the protonolysis of the M‐alkyl bond by surface OH groups and the opening of strained siloxane bridges: the proportion of the two depending on the nature of the metal and its ancillary ligand. Abstract :